ANALISIS RESOLUSI KAMERA DAN SUDUT UNTUK VISUALISASI ALAT MUSIK DRUM MENGGUNAKAN MULTI TRACKING - Afdhol Dzikri; Dwi Ely Kurniawan; Bagus Wardana (Jurnal Teknologi Informasi dan Terapan, 2019)
Music favored by many people. Because the wonderful mix of instruments that can make people become complacent with its voice. One of instrument that favored people that drum. Drum can adrenaline someone for its drum. The introduction of drums still use books or media twodimensional (2D). One of development the introduction of drums could use Augmented Reality (AR). In this study, Augmented Reality is an application that visualizes the shape of parts of the drums. In manufacturing consists of three phases, namely making marker, making 3D objects with Autodesk Maya, and manufacturing of AR application using Unity 3D. In this study using multi tracking method that is able to scan more than one marker simultaneously. Testing of this research was conducted by two parameters, namely, the resolution of the camera, and angle. The resolution parameter consists of 2 Megapixel camera, 3.2 Megapixel, 5 Megapixel, while for angles comprised of 300 , 450 and 900. From the results of these tests showed that the ideal angle for scanning is at an angle of . When using angle and less than 900 , then the time for generating 3D objects can be longer. For the resolution of the camera is a 5 Megapixel recommended, because it can detect the marker faster in comparison with the resolution 2 megapixel camera, and a 3.2 megapixel.